O que dizem surdos e gestores sobre vestibulares em Libras para ingresso em universidades federais - Rocha, Luiz Renato Martins da (Universidade Federal de São Carlos, 2015)
The education of disabled people has been addressed by several public policies arising from important legislative advances over the past few years, which, according to the Higher Education Census data (2001 - 2013), increased the number of enrollments in this type of education, in both public and private spheres. The Decree nº 5626 from 2005 sets outs considerations on bilingual education for deaf people and foresees the possibility of evaluation through alternative mechanisms. Considering this context and focusing on video-recorded entrance examinations in Libras (Brazilian Sign Language), we look for possible answers to the guiding question of this study: what are the impressions of deaf candidates and managers of the entrance examination in Libras, concerning the accessibility barriers (linguistic, cultural and pedagogical) in the admission of students for federal universities? This study aimed to investigate how deaf people who took the video-recorded entrance examination in Libras for two federal universities could comprehend the service addressed to meet their language needs, besides the impressions of the examinations managers. We carried out a qualitative research, exploratory and descriptive, with a semi-structured interview. We translated all the interviews and categorized the data, identifying divergences and convergences within the statements. Authors like Vygotsky (1984, 1989, 1991, 2008), Luria (1980, 1990), Lacerda (1996, 1998, 2000, 2006, 2009, 2012, 2013), Fernandes (2004, 2006, 2008, 2011) and others was adopted as theoretical basis. For methodological design, we used Lacerda (2003), Spink (2000), Costa (2015) and other studies. The results show that deaf people were satisfied with the entrance examination in Libras for both universities since they claim that their linguistic and cultural needs are met. However, accessibility was not enough for everyone to be approved in the examination since there is a deficit in the construction of academic knowledge in the service offered to deaf people in basic education, what needs to be overcome by the realization of high quality education in Brazilian schools. The interviewee also pointed out some technical problems related to the video-recording, which, if taken into account, can guide future actions for the elaboration of entrance examinations in Libras, with a view to expand and improve this service.
Keywords: Vestibular em Libras; Ensino superior; Educação de surdos; Educação especial; Tradução ei ntrepretação em libras; CIENCIAS HUMANAS::EDUCACAO